PENGARUH MODEL PEBELAJARAN TALKING STICK BERBANTUAN MEDIA GAMBAR TERHADAP PEMAHAMAN SISWA PADA MATERI SIMBOL DAN MAKNA SILA PANCASILA KELAS III SD - Febrianti, Lili; Diana Pramesti; Eka Wahyuningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
ABSTRACT Two significant issues that acted as the main focus of this research are the lack of focus and interaction between teachers and students so that the learning process tends to be more one direction and the lack of use of learning models, which affected the students' understanding of the module of Civics Education (PPKN). This research aims to find out whether there is an influence of the talking stick learning model assisted by pictures as its media on the understanding of the symbol and the meaning of the fifth principle of Pancasila among third-grade primary school students. The research design of this study is quantitative research using a quasi- experimental design research method with a non-equivalent control group design. The subjects in this research were the students of third grade in one elementary school, especially 34 students in class IIIA that acted as the experimental group class and 34 students in class IIIB as the control group. The data sampling technique in this research is the total sampling type, while the data collection technique is the test type. Therefore, the test in this research was the ten essay questions. For analysing the data, this research used the normality and homogeneity tests, then continued with hypothesis testing. Based on the results of the normality test and homogeneity test, the data is usually distributed, and both variances are homogeneous. Meanwhile, the result of the hypothesis test showed that the statistical value tcount = 3,132 > table = 1,997As this research showed that Ho is rejected and Ha is accepted. Therefore, there is an influence of the talking stick learning model assisted by pictures as its media on the understanding of the symbol and the meaning of the fifth principle of Pancasila among third-grade primary school students. Keywords: Talking Stick,Pictures, student, understanding